ANALISIS PENERAPAN AKUNTANSI ATAS INSENTIF DAN PEMUTIHAN DENDA PAJAK KENDARAAN BERMOTOR DI PROVINSI SULAWESI UTARA - Kalvaris Gerung Languyu; Treesje Runtu; Pricillia Weku (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Motor Vehicle Tax (PKB) is one of the potential high taxes for regional revenues. Motor Vehicle Tax is included in the type of provincial tax which is part of the Regional Tax where the potential for PKB revenue is 70% of the Regional Original Revenue (PAD). This study aims to analyze the application of accounting for incentives and write-off of Motor Vehicle Tax fines in North Sulawesi Province. The analytical method used in this study is a qualitative descriptive method which aims to describe objective and subjective conditions that occur in the field by explaining the problems encountered based on existing data. The results of the study show that the application of incentives and write-off of motorized vehicle tax fines has been implemented through a by-system and is in accordance with Governor Regulation Number 61 of 2020. In addition, the Regional Revenue Agency has also implemented incentives and write-off of fines for three periods during 2022. Keywords: Motor Vehicle Tax, Incentives and Penalties.